Surviving in the Land of the Dead: Bantu Religion in the Brazilian Diaspora - Holl, Arno Robert (International journal of Latin American religions, 2020)
This paper seeks to identify elements of Bantu religion that, almost 500 years after the arrival of the first Bantu slaves, remain existent in Brazilian culture, especially in AfroBrazilian religions. For this purpose, I will analyze literature on the cosmology of Bantu peoples in Congo and Angola and compare the findings to Afro-Brazilian religious concepts that are known to be of Bantu origin. I then will apply the concepts of Brazilian Modernist Anthropophagy, Amerindian Perspectivism, and form as defined by Eduardo Kohn to try and understand the mechanisms of the survival of Bantu practices in Brazil, where they have been openly discarded and discriminated against for centuries. My goal is to show that the often described passivity and willingness to give up their ways in favor of syncretism and acculturation of Bantu slaves may have been a far more active survival strategy than one might think.